Challenges and risks involved in deploying 6G and NextGen networks - Bharathy, A. M. Viswa, 1986-; Alhadidi, Basim, 1972- (Advances in wireless technologies and telecommunication (AWTT) book series., 2022)
"This book focuses on AI-enabled NextGen (6G and beyond) networks making readers aware of the challenges waiting in NextGen networks, so that proper steps could be taken to either minimize or eliminate issues on 6G and NextGen networks and incorporating AI in NextGen networks for privacy and security policies"--